1987
DOI: 10.1557/proc-98-135
|View full text |Cite
|
Sign up to set email alerts
|

Laser Induced Fluorescence and Optical Emission Studies of Fluorocarbon Plasmas

Abstract: Laser induced fluorescence of CF2 has been observed in plasmas of CF4 and its mixtures with O2 and H2. Surface removal rates of the radical in pure CF4 were measured by observing the decay of the radical when the plasma is switched off. The reduction in CF2 concentration, and the increase in F atom concentrations (the latter measured by optical emission spectroscopy) on the addition of O2 is reproduced by a model of the plasma in which gas phase chemical reactions play a dominant role. The increase in CF2 conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Furthermore, it has been shown that, under strongly polymerizing conditions ͑for ex-ample, in CF 4 plasma with a high H 2 content͒, the lifetime of the CF 2 radical becomes extremely long. [31][32][33] This implies that its reaction probability on the wafer and reactor wall surfaces becomes vanishingly small, and thus that the polymer film is not formed by direct incorporation of incident CF 2 radicals.…”
Section: B the Role Of Cf X Radicalsmentioning
confidence: 99%
“…Furthermore, it has been shown that, under strongly polymerizing conditions ͑for ex-ample, in CF 4 plasma with a high H 2 content͒, the lifetime of the CF 2 radical becomes extremely long. [31][32][33] This implies that its reaction probability on the wafer and reactor wall surfaces becomes vanishingly small, and thus that the polymer film is not formed by direct incorporation of incident CF 2 radicals.…”
Section: B the Role Of Cf X Radicalsmentioning
confidence: 99%
“…However, CF2 did not show a dependence on percent oxygen. This is a surprising result since others have found a marked decrease in CF2 with oxygen, both experimentally and theoretically (6,14,15). This may be due to the underlying spectral continuum centered at 250 nm which is observed in the presence of oxygen.…”
Section: Model Developmentmentioning
confidence: 78%
“…This has led recently to the development of industrial reactors that incorporate hot silicon reactor walls in order to increase and control the polymerization. However, under strongly polymerizing conditions (for example, in CF 4 plasmas with a high H 2 content), the lifetime of the CF 2 radical becomes extremely long [32][33][34]. This implies that its reaction probability on the wafer and reactor wall surfaces becomes very small, and thus that the polymer film is not formed by direct incorporation of incident CF 2 radicals.…”
Section: Cf X Radicalsmentioning
confidence: 99%
“…The pump-out rate (about 1 s −1 ) is also negligible. In contrast, under conditions where the F atom concentration is high, CF x radicals are efficiently destroyed at the grounded reactor walls [27,32,65] (see table 2). This leads to loss rates of the order of 100-1000 s −1 , depending on the radical, the plasma conditions and (especially) the reactor geometry.…”
Section: Fluorine-rich Conditionsmentioning
confidence: 99%